UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN METODE PEMBELAJARAN TEAM GAMES TOURNAMENT - Sarmasuseni Tampubolon (Pusat Riset dan Inovasi Nasional, 2023)
ABSTRACT, The formulation of the problem in this study is whether after implementing the team games team games tournament learning method can improve student learning outcomes in Class VI SD Negeri 177041 Simarhompa. The number of subjects in this study were 21 students from Class VI in the 2021/2022 school year. To obtain data in this study, the authors conducted data collection research by means of a member test. This type of research is classroom action research (CAR) using an inquiry learning model. This study consisted of 2 cycles, cycle I and cycle II, each of which had two meetings. At each meeting the researchers conducted a test of student learning outcomes, to determine the level of student learning completeness. In cycle I for the class average value of 79.18% in cycle II increased to 83.04% or an increase of 3.86%. The results of the study show that through the application of team games team games tournament learning methods can improve student learning outcomes in Class VI SD Negeri 177041 Simarhompa